2016
DOI: 10.20884/1.jm.2016.11.2.220
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Power Variations on Selectivity of Synthesis Reaction of 2’-Hydroxychalcone Analogue Under Microwave Irradiation

Abstract: Some 2’-hydroxychalcone analogues have been widely used as an intermediate to synthesize various heterocyclic compounds, such as flavanones, flavanonols, flavones, flavonols and others. The heterocyclic compounds are also known to have a variety of interesting bioactivities in the medicinal chemistry and also have potency to be applied  in material chemistry including in industry. Therefore, 2’-hydroxychalcone analogues are often synthesized by researchers as intermediate, both in research associated with drug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…The activity of 10 synthesizable compounds of the top 20 hit compounds was evaluated by in vitro assay against T47D human breast cancer cell lines. These compounds were synthesized by Zamri and coworkers 49…”
Section: Resultsmentioning
confidence: 99%
“…The activity of 10 synthesizable compounds of the top 20 hit compounds was evaluated by in vitro assay against T47D human breast cancer cell lines. These compounds were synthesized by Zamri and coworkers 49…”
Section: Resultsmentioning
confidence: 99%
“…The 1 H NMR spectrum of compound 3F showed a characteristic chemical shift when compared to the spectrum of the starting material (CM). Based on the literature, the hydroxyl group (2'-OH) of compound CM in CDCl3 always give a typical singlet signal at a chemical shift of 12-13 ppm (Zamri et al, 2016). Thus, the absence of this signal in the 1 H NMR spectrum of the product 3F indicated that the 2'-OH group successfully undergo cyclization to form a flavonoid heterocyclic ring (Zamri et al, 2016).…”
Section: Dockingmentioning
confidence: 97%
“…Based on the literature, the hydroxyl group (2'-OH) of compound CM in CDCl3 always give a typical singlet signal at a chemical shift of 12-13 ppm (Zamri et al, 2016). Thus, the absence of this signal in the 1 H NMR spectrum of the product 3F indicated that the 2'-OH group successfully undergo cyclization to form a flavonoid heterocyclic ring (Zamri et al, 2016). In addition, another peculiarity is the appearance of a single peak at a chemical shift of 7.04 ppm with 1H integration which indicated the presence of a proton from the hydroxyl group (3-OH) attached to the C3 carbon of chromen ring.…”
Section: Dockingmentioning
confidence: 99%
“…As a consequence, further separation is necessary. 12 Chalcones synthesis was observed under ultrasound irradiation for a notable enhancing effect on the time of reaction and yield. 13 In this study, some chalcone derivatives (compound 1-8) were succesfully synthesized using classical Claisen-Schmidt condensation by reacting 2-hydroxyacetophenone and some substituted benzaldehydes using NaOH 40% (Fig.…”
Section: Introductionmentioning
confidence: 99%